The Influence of Human Resources, Facilities and Infrastructure To Hemodialization Patient Satisfaction in Bhayangkara Hospital TK. 1 Raden Said Soekanto Jakarta - Kesty Rama Danty (AFEBI Management and Business Review, 2019)
Hemodialysis is one type of therapy for kidney failure patients that many suffer from in Indonesia. Identification of problems in this study consisted of a lack of nurses and non-medical staff working in the Hemodialysis room, lack of facilities and infrastructure in Hemodialysis rooms such as toilets for visitors, narrow hemodialysis space so that beds between patients were close together, consultation room for patients with doctors, the location of Hemodialysis rooms is less strategic than major roads, and there is no isolation room specifically for Hepatitis B patients. Phenomena that often occur in some hospitals, especially related to the ability of human resources in caring for patients who already have Hemodialysis training certificates as a benchmark for the ability of ideal and actual human resources. Another problem is that the application of technology that has not been optimal has an effect on patient satisfaction, an environment that is not yet conducive which has an effect on patient satisfaction and the provision of incentives to HD room staff is inadequate which influences service and impacts patientThis research is needed to study and analyze how much influence human resources and facilities and infrastructure have on the satisfaction of hemodialysis patients at TK I Raden Said Soekanto Bhayangkara Hospital, Jakarta. The design of the research is using descriptive analysis and regression analysis. To meet the research objectives set, the research design used a survey method with a quantitative approach using questionnaires to collect data. The construction of a questionnaire or list of questions is based on perception.The results showed a positive and significant relationship between Human Resources and Hemodialysis Patient Satisfaction at Bhayangkara Tk.I Hospital, Soekanto Hospital, East Jakarta. Correlation of test results in the form of strong positive results. Human resources have a contribution of 42.6% to patient satisfaction. The results also showed a positive and significant relationship between Facilities and Infrastructure on Hemodialysis Patient Satisfaction at Bhayangkara Tk.I Hospital, Soekanto Hospital, East Jakarta. Correlation of test results in the form of strong positive results. Facilities and infrastructure contributed 43.7% to patient satisfaction. The results showed a positive and significant relationship between human resources and infrastructure simultaneously to Hemodialysis Patient Satisfaction at Bhayangkara Tk.I Hospital, Soekanto Hospital, East Jakarta. Human resources and infrastructure simultaneously contribute 56.9% to patient satisfaction.